Effects Of Tea Leaf-Based Diets On The Growth And Reproduction In Two Tropical Earthworm Species (Pontoscolex Corethrurus And Drawida Assamensis) (Applied Biological Research, 2019)
A laboratory-based experiment was conducted to study the effect of tea leaf based diets on the growth and reproduction intwo dominant earthworm  species (Pontoscolex corethrurus and Drawida assamensis) of tea plantations  in Tripura (India). Among the four different diets [soil (S); soil-tea leaf (ST);  soil-cow dung (SC) and soil-tea leaf-cow dung (STC)], P. corethrurus maintained significant higher growth rate than native species, D. assamensis in each diet. Growth rate was highest in SC for both P. corethrurus (11.35 mg  worm-1 day-1) and D. assamensis (10.70 mg worm-1 day-1). Cocoon appeared  in all the experimental culture pots, except in ST with D. assamensis. In both  the species, growth rate was lowest in S and ST. Among all the experimental  diets, both the earthworm species produced highest number of cocoons in SC  diet for the whole experimental period (150 days). The rate of juvenile  production in P. corethrurus (0.82 juvenile worm-1 week-1) was significantly  higher than those in D. assamensis (0.28 juvenile worm-1 week-1). The  experiment clearly indicates that for vermiculture of these two geophagous  earthworm species, cow dung is preferred to tea leaf-based diets probably  because of rich content of polyphenols in latter.
Keywords: Cocoon; cow dung; growth; P. corethrurus; D. assamensis; reproduction; tea leaf